Optimizing village empowerment through creative MSMEs, financial literacy, and government policies for poverty alleviation - Wahyu Wibowo; Mega Rahmawati; Taufikur Rohman; Nasrudin Nasrudin; Zakiyudin Fikri (Priviet Social Sciences Journal, 2026)
This study examines village empowerment strategies for poverty alleviation through the integration of strengthening creative MSMEs based on local culture, increasing financial literacy (including digital financial literacy), and government policy support. The study uses a literature study by selecting and synthesizing research findings related to the concept of Cultural Independent Villages, creative entrepreneurship, financial inclusion, and collaborative governance models. The results of the synthesis show that local culture can be an endogenous capital that generates economic added value through creative products and services, while strengthening citizen participation. However, the growth of MSMEs is not sustainable without the ability to record finances, plan capital, and utilize secure digital financial services. Policy support is needed to build an ecosystem in the form of tiered mentoring, business incubation, pentahelix partnerships, access to financing, and market access through marketing digitalization. The study confirms that fragmented interventions tend to produce short-term impacts, so programs should be designed place-based with success indicators that include revenue, business sustainability, market expansion, and financial inclusion. Future agendas include cross-village integrative model testing, data-driven impact measurement, and risk and consumer protection assessments on digital financial literacy. Practically, the main recommendations are to build an applicable financial literacy curriculum, facilitate legality and product standardization, and strengthen culture-based branding so that MSMEs upgrade and their benefits are evenly distributed at the household level.